2016
DOI: 10.11648/j.ajhr.20160401.12
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude and Practice of Mothers Towards Immunization of Infants in Health Centres at Addis Ababa, Ethiopia

Abstract: Abstract:Background: In Ethiopia, a considerable proportion of childhood morbidity and mortality is due to vaccine preventable diseases. According to EDHS 2011, only 24% of children were fully vaccinated nationally. Mothers' knowledge, attitude and practice are key tools to decrease dropout rates and to prevent or control infectious diseases. Thus, this study was aimed to assess Knowledge, Attitude and Practice of mothers regarding infant immunization and their associated factors in immunization clinic in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
31
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 9 publications
(19 reference statements)
9
31
7
Order By: Relevance
“…Also, immunization has shown major aspects of disease, disability and death prevention. The most common vaccine preventable diseases are Rubella, measles, diphtheria, Tetanus, pertussis and Polio (1,2) . Giving the child the appropriate vaccine would significantly decrease the costs of disease treatment and rates of disease thus enhance a good quality of life for children (3) .…”
Section: Introductionmentioning
confidence: 99%
“…Also, immunization has shown major aspects of disease, disability and death prevention. The most common vaccine preventable diseases are Rubella, measles, diphtheria, Tetanus, pertussis and Polio (1,2) . Giving the child the appropriate vaccine would significantly decrease the costs of disease treatment and rates of disease thus enhance a good quality of life for children (3) .…”
Section: Introductionmentioning
confidence: 99%
“…25 Nearly 5% of the respondents have not receive the T.T vaccine in their previous pregnancy similar to the study from Ethiopia. 32 The underlying reason of not vaccinating the children and not taking T.T vaccine should be rule out so as to plan the interventions accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that women's awareness of community conversation program is the predictor of full immunization (37). Another study also reported that 55%, 53.8%, and 84% of respondents had good knowledge, positive attitude, and good practice towards immunization of infants, respectively (49).…”
Section: Community Engagement In Immunization Programmentioning
confidence: 99%